Pengaruh Social Media Marketing Dan Kualitas Produk Terhadap Keputusan Pembelian Di Toko Eldra Pratama Melalui Minat Sebagai Variabel Intervening - Eldra, Muhammad Alif Febrinka; Iskandar, Donant Alananto (Research and Community Service UNIVERSITAS KALBIS, 2025)
The purpose of this study is to determine the influence of social media marketing, product quality on purchasing decisions through interest as an intervening in Eldra Pratama stores. This study used validity tests, reliability tests, multiple linear regression tests and hypothesis tests both partial and simultaneous with the help of the SPSS version 22. A sample of 122 respondents was taken. The study used a quantitative approach with purposive sampling techniques. Data collection was done by distributing questionnaires using the Likert scale to measure each statement. The results showed that there was a positive and significant influence between social media marketing, product quality and purchasing decisions through interest as an intervention in the Eldra Pratama store.